Apresiasi Komunikasi dalam Komunikasi Antarpribadi - YUANITA SETYASTUTI (Komunikator, 2012)
The purpose of this study is to determine the difference of communication apprehension among undergraduate students of communication science study program, Faculty of Social and Political Sciences, Lambung Mangkurat University based on communication context and extrovertintrovert of personality types. The method of this research is quantitative method and comparative study. The data was collected by Para Tingkat questionnaire of Situational Communitaion Apprehension by Devito () and extrovert-introvert MBTI personality type test by Myers (). The samples were 80 undergraduate students. The data were analyzed by One Way Anova and independent sample T-Test. In analyzing the data, it also used SPSS 18.00. The result of this study is that there are significant differences of communication apprehension among undergraduate students of communication science study program, Faculty of Social and Political Sciences, Lambung Mangkurat University based on communication context with F 11,415 and p 0.000 0,050. Thus, hypothesis 1 is accepted. There is no significant difference of communication apprehension among students based on extrovertintrovert extrovertintrovert personality type with F 0.115 and p 0.734 0.050. So, hypothesis 2 is rejected. Keywords: Level of Communication Apprehension, Communication Context, Extrovert-Introvert, Personality Type